2017
DOI: 10.9775/kvfd.2017.18805
|View full text |Cite
|
Sign up to set email alerts
|

Enfeksiyöz Laringotraheitis İle Doğal Enfekte Yumurta Tavuklarında Solunum Kanalı Lezyonları Üzerine İmmunohistokimyasal Çalışmalar

Abstract: In this study, naturally infected by Gallid Herpesvirus type-1 in laying hens to be diagnosed by pathological and PCR methods. Sixty pieces of hens were collected in coops from Central Anatolia region. After necropsy, routine pathological processes were applied to the trachea/ larynx, sinuses, lungs and air sacs. All organs were also stained by immunoperoxidase method, and PCR methods were applied to formalin fixed paraffin embedded (FFPE) tissues. Immunohistochemically, the positivities were seen in trachea/l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…In the present study, the immunohistochemical analysis was showed a high sensitivity through the detection of immunoreactivity and the distribution of ILTV antigen in the syncytial cells, inflammatory cells and epithelial cells of larynx, trachea and lung is used to confirm the occurrence of the disease allowing visualization of viral antigen distributed in different tissues cannot be predicted by PCR as mentioned by Fuchs et al (7). Highest IHC positivity has always been found in the trachea and lung as reported by Yavuz et al (34).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…In the present study, the immunohistochemical analysis was showed a high sensitivity through the detection of immunoreactivity and the distribution of ILTV antigen in the syncytial cells, inflammatory cells and epithelial cells of larynx, trachea and lung is used to confirm the occurrence of the disease allowing visualization of viral antigen distributed in different tissues cannot be predicted by PCR as mentioned by Fuchs et al (7). Highest IHC positivity has always been found in the trachea and lung as reported by Yavuz et al (34).…”
Section: Discussionsupporting
confidence: 53%
“…We consider the anatomopathological examination as the primary diagnostic tool and plays an important role in the diagnosis of ILTV infection, particularly in the acute phase of the viral infection by observation of multinucleated syncytial cells containing intranuclear eosinophilic inclusion bodies, a pathognomonic finding for ILTV infection (23,34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations